Relative age effect in handball players of Murcia: Influence of sex and category of game - Gómez-López, M.; Angosto Sánchez, S.; Granero-Gallegos, A.; Chirosa Rios, L. J. (Journal of Human Sport & Exercise, 2017)
This study aimed to analyze the evolution of the relative age effect on federal handball players in the Region of Murcia. In order to achieve this goal, the sex, date of birth, and category data of 845 federated game players from different teams in the 2013/2014 season and those of 1043 players in the 2015/2016 season were analyzed, performing comparisons and studying differences by means of ?2 and Z tests and the Bonferroni method. The analysis of results by trimester and semester of birth revealed that, while there were no statistically significant differences in terms of the season and game category differences, differences were found in terms of sex. The results also confirmed a greater distribution of male players in the second semester and of female players in the first semester. Therefore, it seems to confirm a trend related to the effect of the relative age on federated handball players in Murcia.